Dynamics of Multicultural Education in Indonesia - Jaswan Jaswan; St. Wardah Hanafie Das (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Multicultural education in Indonesia is an important approach to creating an inclusive and harmonious society, considering the ethnic, cultural, and religious diversity that exists in the country. This research aims to explore the dynamics of multicultural education, the challenges faced in its implementation, and provide recommendations for educational policies and practices. The method used is library research, with thematic analysis of various relevant literature. Key findings suggest that while multicultural education has great potential to build tolerance and mutual understanding, its implementation is still hampered by a lack of understanding among educators and limited resources. Concrete examples of multicultural educational practices in some schools show that with the right approach, this education can have a positive impact on student attitudes. The resulting recommendations include improved training for teachers, curriculum revision, and collaboration with the community. The study also identified the need for further studies to explore the long-term impact of multicultural education and its comparison with practices in other countries. By overcoming the existing challenges, it is hoped that multicultural education can be implemented more widely and have a positive impact on future generations in Indonesia.